Pengaruh Perencanaan dan Efektifitas Penggunaan Dana Desa Terhadap Pembangunan Desa Negara Batin (Studi Pada Kecamatan Negara Batin Kabupaten Way Kanan) - Ulandari, Resti; Tarmizi, Rosmiati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Negara Batin is a village located in the regent Way Kanan. The village government's concern for the facilities and infrastructure of the village is very important to achieve the welfare of the village community. Planning and effective use of village funds are necessary to support the development of Negara Batin Village. Therefore, if the use of village funds can be planned and implemented effectively, it will bring great benefits to the residents of Negara Batin Village in Way Kanan Regency. The purpose of this study is to determine whether planning and efficiency in the use of village funds affect the development of Negara Batin village. The type of research used in this study is quantitative research. The population used is the village of Negara Batin, regent Way Kanan. The sampling technique used was probability sampling using the Slovin formula, such that a sample of 98 respondents was obtained. Data collection was carried out through literature research, documents, observations, interviews, and questionnaires. The data analysis tools used include several linear regression tests, correlation coefficient tests, t-tests, F-tests, and R^2 tests. Based on the research results, effective planning and use of village funds has a positive and significant impact on the development of Negara Batin village. Effective planning and utilization of village funds contributed 36.5% to the development of Negara Batin Village in Negara Batin District, Way Kanan Regency. Meanwhile, the remaining 63.5% are affected by other factors that have not been considered in this study.